Enhanced Methane Oxidation Potential of Landfill Cover Soil Modified with Aged Refuse - Haijie He; Tao Wu; Zhanhong Qiu; Chenxi Zhao; Shifang Wang; Jun Yao; Jie Hong (Atmosphere, 2022)
Aged refuse with a landfill age of 1.5 years was collected from a municipal solid waste landfill with high kitchen waste content and mixed with soil as biocover material for landfill. A series of laboratory batch tests was performed to determine the methane oxidation potential and optimal mixing ratio of landfill cover soil modified with aged refuse, and the effects of water content, temperature, CO2/CH4, and O2/CH4 ratios on its methane oxidation capacity were analyzed. The microbial community analysis of aged refuse showed that the proportions of type I and type II methane-oxidizing bacteria were 56.27% and 43.73%, respectively. Aged refuse could significantly enhance the methane oxidation potential of cover soil, and the optimal mixing ratio was approximately 1:1. The optimal temperature and water content were about 25 °C and 30%, respectively. Under the conditions of an initial methane concentration of 15% and an O2/CH4 ratio of 0.8–1.2, the measured methane oxidation rate was negatively correlated with the O2/CH4 ratio. The maximum methane oxidation capacity measured in the test reached 308.5 (μg CH4/g)/h, indicating that the low-age refuse in the landfill with high kitchen waste content is a biocover material with great application potential.